Research progress on the mechanism of curcumin anti-oxidative stress based on signaling pathway - Cui, Jie; Li, Haonan; Zhang, Tianyi; Lin, Fengli; Chen, Meiyun; Zhang, Guimin; Feng, Zhong (Frontiers in Pharmacology, 2025)
Oxidative stress refers to an imbalance between oxidative capacity and antioxidant capacity, leading to oxidative damage to proteins, lipids, and DNA, which can result in cell senescence or death. It is closely associated with the occurrence and development of various diseases, including cardiovascular diseases, nephropathy, malignant tumors, neurodegenerative diseases, hypertension, diabetes, and inflammatory diseases. Curcumin is a natural polyphenol compound of β-diketone, which has a wide range of pharmacological activities such as anti-inflammatory, antibacterial, anti-oxidative stress, anti-tumor, anti-fibrosis, and hypolipidemic, demonstrating broad research and development value. It has a wide range of biological targets and can bind to various endogenous biomolecules. Additionally, it maintains the redox balance primarily by scavenging ROS, enhancing the activity of antioxidant enzymes, inhibiting lipid peroxidation, and chelating metal ions. This paper systematically describes the antioxidative stress mechanisms of curcumin from the perspective of signaling pathways, focusing on the Keap1-Nrf2/ARE, NF-κB, NOX, MAPK and other pathways. The study also discusses potential pathway targets and the complex crosstalk among these pathways, aiming to provide insights for further research on curcumin’s antioxidant mechanisms and its clinical applications.